The brother-in-law effect - Levine, David K. (2010)
When a firm is forced to pay abnormally high wages, hiring transfers rents. This effectively endows the employer with the ability to grant favors, and he may wish to do so even at some cost to efficient production. We refer to this as the brother-in-law effect. This article analyzes its consequences. When the brother-in-law effect is due to unionization, decisions regarding both the number and type of workers employed could be inefficient; overemployment could obtain even relative to the workforce that would be employed without unionization. We also identify cases in which nepotism improves efficiency.